Dandelion Tea is Effective at Killing Cancer Cells - Cock, Ian E; Cock, Esther SG (Pharmacognosy Communications)
Plant species of the genus Taraxacum (commonly known as dande- lion) have a long history of use in the treatment of a myriad of medical conditions including uses for the eradication of pathogenic disease, the treatment of liver complaints and as a diuretic.1 A recent study from re- searchers at the University of Windsor in Ontario, Canada has reported that dandelion root extracts are also effective in fighting cancer.2-6 Of particular note, dandelion root extracts induced apoptosis in a chronic myeloid leukaemia cell line.5 That finding was noteworthy as the cell line tested was particularly aggressive and is resistant to many other cancer chemotherapy agents. The research team have also trialled the extract on other leukaemia cell lines,2 as well as melanoma3 and pancreatic cancer4 cells with similar results. Whilst this finding is promising for people with these diseases, the authors of the study have urged caution. Bioactive compounds within the dandelion root may interfere with conventional cancer chemotherapies. It is therefore important that patients do not mix the natural remedy with conventional chemotherapies without close medical supervision and that patients notify their medical practitioners if they intend to use dandelion root formulations for these purposes.